Effect of E-Loyalty Cues on Repurchase Behavioural Intentions Among Online Shoppers - Kurup, Ajit J.; Jain, Priyanka (Indian Journal of Marketing, 2018)
The Indian e-commerce industry has made rapid strides due to increasing Internet connectivity, better technology, growing young population, and greater access to smart phones and other mobile devices. The acquisition of Flipkart by U.S. retail giant Walmart for 16 billion was a precursor to the increased consolidation in the online-retail market space in India. The country today has become a highly competitive market for both these international players and home-grown e-tailers. It is imperative for all the players to carve out a niche for themselves in the market and differentiate their offerings to have a loyal consumer base. This study used structured equation modelling to determine cues that lead to e - loyalty, which eventually results in customers repurchasing from the same e-tailer. Data were collected from 317 online consumers using a structured questionnaire, which showed that product offerings, convenience, past purchase experience, and web-store environment had a significant impact on e - loyalty. Convergent and discriminant validities were established through confirmatory factor analysis. The overall model fitment was established by validating the structural model and hypothesized relationships. The findings highlighted the importance of e - loyalty and its influence on repurchase behaviour. This research provided important insights into the minds of the Indian consumer and provided details about which areas the e-tailors need to focus upon to maintain their competitive edge in the market.